2015
DOI: 10.1177/2055102915598089
|View full text |Cite
|
Sign up to set email alerts
|

The psychometric properties of the WHOQOL-BREF in Japanese couples

Abstract: This study investigated the psychometric properties of the Japanese version of the WHOQOL-BREF among 10,693 community-based married Japanese men and women (4376 couples) who were either expecting or raising a child. Analyses of item-response distributions, internal consistency, criterion validity, and discriminant validity indicated that the scale had acceptable reliability and performed well in preliminary tests of validity. Furthermore, dyadic confirmatory factor analysis revealed that the theoretical factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
5
7
1
Order By: Relevance
“…The WHOQOL-BREF showed high internal consistency, and the fit of the hypothesized four domains of QOL was acceptable. In addition, the pattern of weak and strong standardized regression coefficients was consistent with previous research [13,20,21]. Weak standardized regression coefficients were found in reversed items (i.e., pain, medication, and negative feelings), while some domains seemed to make more important contributions to QOL (e.g., activities, work, self-esteem, spirituality) than others.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The WHOQOL-BREF showed high internal consistency, and the fit of the hypothesized four domains of QOL was acceptable. In addition, the pattern of weak and strong standardized regression coefficients was consistent with previous research [13,20,21]. Weak standardized regression coefficients were found in reversed items (i.e., pain, medication, and negative feelings), while some domains seemed to make more important contributions to QOL (e.g., activities, work, self-esteem, spirituality) than others.…”
Section: Discussionsupporting
confidence: 89%
“…The data fit the hypothesized four-domain model after four error covariances were added to the model, χ 2 (244) = 3962.404, p < .001, SRMR = .044, RMSEA = .067, CFI = .902. These error covariances had been identified in previous research [12,13,[19][20][21][22][23]. Standardized regression coefficients were significant, p < .001, (Fig.…”
Section: Construct Validitysupporting
confidence: 78%
“…Bref is commonly reported in the literature, 7,9,10,13,16,18,34 because this instrument is short and recommended by the WHO. 13 The CFA showed that the original model of the WHOQOL-Bref did not show good fit to the study samples, and some modifications were performed.…”
Section: Evaluation Of Quality Of Life Using the Whoqol-mentioning
confidence: 99%
“…In another study, Najafi et al 17 highlighted that the content of item 8 was not clear. The WHOQOL Group, 13 Fu et al, 8 and Yoshitaki et al 16 also performed some fits in the WHOQOL-Bref, such as correlation between items 3 and 4 errors. Those authors reported that items 3 and 4 neither have adequate convergent validity nor strong enough factorial weights.…”
Section: Evaluation Of Quality Of Life Using the Whoqol-mentioning
confidence: 99%
See 1 more Smart Citation